27.2: Invited Paper: True 3D displays for AR applications. (28th November 2018) - Li, Yan; Liu, Shuxin; Zhou, Pengcheng; Chen, Quanming; Su, Yikai
Abstract : Augmented reality (AR) technology, which integrates virtual computer‐generated information into the real world scene, is believed to be the next‐generation human‐machine interface. However, most AR products adopt stereoscopic 3D display technique, which causes the accommodation‐vergence conflict. To solve this problem, we have proposed two approaches. The first is a multi‐planar volumetric display using fast switching polymer‐stabilized liquid crystal (PSLC) films. By rapidly switching the films between scattering and transparent states while synchronizing with a high‐speed projector, the 2D slices of a 3D volume could be displayed in time sequence. We delved into the research on developing high‐performance PSLC films in both normal mode and reverse mode; moreover, we also realized the demonstration of four‐depth AR images with correct accommodation cues. For the second approach, we realized a holographic AR display using digital blazed gratings and a 4f system to eliminate zero‐order and higher‐order noise. With a 4k liquid crystal on silicon device, we achieved a field of view (FOV) of 32 deg. Moreover, we designed a compact waveguide‐based holographic 3D display. In the design, there are two holographic optical elements (HOEs), each of which functions as a diffractive grating and a Fresnel lens. Because of the grating effect, holographic 3D image light is coupled into and decoupled out of the waveguide by modifying incident angles. Because of the lens effect, the collimated zero order light is focused at a point, and got filtered out. The optical power of the second HOE also helps enlarge FOV.